Characterization of Evanescent Field Gas Sensor Structures Based on Silicon Photonics - Christian Ranacher; Cristina Consani; Natalie Vollert; Andreas Tortschanoff; Markus Bergmeister; Thomas Grille; Bernhard Jakoby (IEEE Photonics Journal)
Photonic sensors that operate in the mid-infrared spectral range are an emerging field for photonic microsystems. In this paper, we present a photonic gas sensor concept based on silicon waveguides using infrared evanescent field absorption. The waveguides were specifically designed for CO $_{2}$ sensing at a wavelength of $λ ={\text{4.26}}\,μ m$ as possible application for the proposed sensor platform. The waveguide cross section as well as the substructure were investigated using finite-element simulations and the devised structures were fabricated using mass fabrication processes exclusively. In order to evaluate the potential for long interaction path lengths using polysilicon strip waveguides, a study on the intrinsic losses of polysilicon waveguides was conducted. The lowest intrinsic damping that was obtained for polysilicon strip waveguides was 3.98 dB/cm. Furthermore, the sensing capability of the devised waveguides was tested with quantitative CO $_{2}$ measurements down to a concentration of 500 ppm CO $_{2}$ . From the quantitative measurements, the evanescent field ratio was estimated and was in the range between $η ={\text{14}{%}}\hbox{--}{\text{16}{%}}$ .